2013
DOI: 10.1111/add.12274
|View full text |Cite
|
Sign up to set email alerts
|

Pain is associated with heroin use over time in HIV‐infected Russian drinkers

Abstract: Aims This study evaluated whether pain was associated with increased risk of using heroin, stimulants or cannabis among HIV-infected drinkers in Russia. Design Secondary analysis of longitudinal data from the HERMITAGE study, a behavioral randomized controlled trial, with data collected at baseline, 6 month and 12 month visits. Setting Recruitment occurred at HIV and addiction treatment sites in St. Petersburg, Russian Federation. Participants Six-hundred and ninety-nine HIV-infected adult drinkers. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 59 publications
(79 reference statements)
1
18
0
Order By: Relevance
“…We previously reported an association between pain and heroin use over time in this sample (Tsui et al, 2013). Although alcohol has weaker analgesic properties, it is legal and much more widely available.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…We previously reported an association between pain and heroin use over time in this sample (Tsui et al, 2013). Although alcohol has weaker analgesic properties, it is legal and much more widely available.…”
Section: Introductionmentioning
confidence: 61%
“…A study of 1,940 HIV-infected men in the United States found that pain was significantly associated with cannabis and hard drug use defined as cocaine or heroin use (Tsao et al, 2011), and we previously reported an association between pain and heroin use in this same Russian sample (Tsui et al, 2013). A prior study conducted in a population of homeless, HIV-infected persons in San Francisco that examined bivariate associations between substance use and pain severity did not find differences in the proportion reporting current daily drinking among pain severity categories (Miaskowski et al, 2011).…”
Section: Discussionmentioning
confidence: 83%
“…Chronic pain is highly relevant to substance use outcomes, as it may serve as a barrier to treatment entry, retention or success, and a trigger for relapse. Among HIV-infected substance users, pain has been associated with persistent use of heroin (Tsui et al, 2013). In some studies, patients with chronic pain who received addiction treatment were more likely to relapse to drug use compared to patients without pain (Caldeiro et al, 2008; Larson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of chronic pain among persons with opioid use disorders treated with opioid agonist therapy (OAT) ranges from 36 to 61% (Barry et al, 2009, 2013; Jamison et al, 2000; Rosenblum et al, 2003). Chronic pain is problematic for patients with substance use disorders as it has been associated with risk for persistent heroin use (Potter et al, 2010; Tsui et al, 2013) and relapse to use of drugs and alcohol (Larson et al, 2007). However, treatment for opioid use disorders with OAT can lead to alterations in pain sensitivity leading to hyperalgesia.…”
Section: Introductionmentioning
confidence: 99%